Analysis of fibrosis in control or pressure overloaded rat hearts after mechanical unloading by heterotopic heart transplantation - Schaefer, Andreas (Sci Rep, 2019)
Mechanical unloading (MU) by implantation of left ventricular assist devices (LVAD) has become clinical routine. This procedure has been shown to reverse cardiac pathological remodeling, with the underlying molecular mechanisms incompletely understood. Most studies thus far were performed in non-standardized human specimens or MU of healthy animal hearts. Our study investigates cardiac remodeling processes in sham-operated healthy rat hearts and in hearts subjected to standardized pathological pressure overload by transverse aortic constriction (TAC) prior to MU by heterotopic heart transplantation (hHTx/MU). Rats underwent sham or TAC surgery. Disease progression was monitored by echocardiography prior to MU by hHTx/MU. Hearts after TAC or TAC combined with hHTx/MU were removed and analyzed by histology, western immunoblot and gene expression analysis. TAC surgery resulted in cardiac hypertrophy and impaired cardiac function. TAC hearts revealed significantly increased cardiac myocyte diameter and mild fibrosis. Expression of hypertrophy associated genes after TAC was higher compared to hearts after hHTx/MU. While cardiac myocyte cell diameter regressed to the level of sham-operated controls in all hearts subjected to hHTx/MU, fibrotic remodeling was significantly exacerbated. Transcription of pro-fibrotic and apoptosis-related genes was markedly augmented in all hearts after hHTx/MU. Sarcomeric proteins involved in excitation-contraction coupling displayed significantly lower phosphorylation levels after TAC and significantly reduced total protein levels after hHTx/MU. Development of myocardial fibrosis, cardiac myocyte atrophy and loss of sarcomeric proteins was observed in all hearts that underwent hHTX/MU regardless of the disease state. These results may help to explain the clinical experience with low rates of LVAD removal due to lack of myocardial recovery.